PENGARUH UTANG LUAR NEGERI DAN BEBAN PEMBAYARAN BUNGA TERHADAP STABILITAS KEUANGAN DI INDONESIA: PERSPEKTIF DEBT SUSTAINABILITY THEORY - Ulfayanti Ulfayanti; Muhammad Syafri (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
This study aims to analyze the influence of foreign debt and interest payments on financial stability in Indonesia from the perspective of Debt Sustainability Theory. The method used is a quantitative approach with secondary time series data obtained from Statistics Indonesia (BPS), Bank Indonesia (BI), and the Ministry of Finance. Data analysis uses multiple linear regression to determine the effect of independent variables on the dependent variable. The results indicate that foreign debt and interest payments impact financial stability, with increasing debt and interest payments potentially putting pressure on fiscal conditions and economic stability. Therefore, sustainable debt management is necessary to avoid long-term risks to the economy